RAM‐SCB Runs on Request at CCMC - Steven K. Morley; Vania K. Jordanova; Yihua Zheng; Maksym Petrenko (Space Weather)
Abstract The Ring current–Atmosphere interactions Model (RAM) with Self‐Consistent magnetic (B) field (SCB) combines a large‐scale kinetic model of ring current plasma with a three‐dimensional (3‐D) force‐balanced model of the terrestrial magnetic field. RAM‐SCB simulates the evolution of major ion species (H+, O+, and He+ by default) and electrons as a function of azimuth, radial distance, energy, and pitch angle. Simulation outputs include the Dst index, and pressure and differential flux of the modeled species, thus providing benefit as a science code and to inform surface charging hazard within the model domain. Version 2.2 of this open‐source simulation code has now—as of 8 August 2023—been made available for Runs‐On‐Request via the Community Coordinated Modeling Center.